Pemanfaatan Media Microsoft Power Point dalam Pembelajaran Kemahiran Berbahasa Arab pada Era Digital - Mabruri Mabruri; Hamzah Hamzah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Life in the Digital Age is automatically required by someone not to be out of date with a device or device such as a computer or laptop. Data and information even the basic needs of a student can be said to have been stored in a system called a digital system. Everything is available in one system that can and is freely accessed by anyone. as a teacher in utilizing sophisticated tools in this digital age, it is demanded to adjust and apply in the form of a learning as the medium. So one of the things that can be used by a teacher is to use Microsoft Power Point program as a medium in innovating a learning. This paper aims to develop an Arabic learning media by using Microsoft Power Point program as a medium in learning Arabic proficiency.